2007
DOI: 10.1074/jbc.m707267200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity of Y-class DNA Polymerase DPO4 from Sulfolobus solfataricus with Templates Containing the Hydrophobic Thymine Analog 2,4-Difluorotoluene

Abstract: The 2,4-difluorotoluene (DFT) analog of thymine has been used extensively to probe the relative importance of shape and hydrogen bonding for correct nucleotide insertion by DNA polymerases. As far as high fidelity (A-class) polymerases are concerned, shape is considered by some as key to incorporation of A(T) opposite T(A) and G(C) opposite C(G). We have carried out a detailed kinetic analysis of in vitro primer extension opposite DFT-containing templates by the trans-lesion (Y-class) DNA polymerase Dpo4 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 41 publications
(78 reference statements)
4
50
0
Order By: Relevance
“…Additionally, the fact that there has not been a reported type II structure containing a 0 templating natural pyrimidine can arguably be considered evidence, by default, that the Ϫ1 frameshift mutation is unfavored by Dpo4 in these cases. Stacking potential and not necessarily a larger relative stacking surface may also lead to increased Ϫ1 frameshift mutations, as was inferred by the recently solved type II crystal structure of a 0 templating hydrophobic thymidine isostere 2Ј-deoxy-2,4-difluorotoluyl with an incoming dA:dGTP pair at the ϩ1 position (34). Overall, the data suggest that the energy supplied by the increased stacking surface and/or stacking potential of the 0 template base and the accompanying hydrogen bonds formed between the incoming base and ϩ1 base combine to provide sufficient stability to counter the large contortions of the active site that occur when the dNTP is positioned opposite the ϩ1 base.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the fact that there has not been a reported type II structure containing a 0 templating natural pyrimidine can arguably be considered evidence, by default, that the Ϫ1 frameshift mutation is unfavored by Dpo4 in these cases. Stacking potential and not necessarily a larger relative stacking surface may also lead to increased Ϫ1 frameshift mutations, as was inferred by the recently solved type II crystal structure of a 0 templating hydrophobic thymidine isostere 2Ј-deoxy-2,4-difluorotoluyl with an incoming dA:dGTP pair at the ϩ1 position (34). Overall, the data suggest that the energy supplied by the increased stacking surface and/or stacking potential of the 0 template base and the accompanying hydrogen bonds formed between the incoming base and ϩ1 base combine to provide sufficient stability to counter the large contortions of the active site that occur when the dNTP is positioned opposite the ϩ1 base.…”
Section: Discussionmentioning
confidence: 99%
“…A ternary complex was subsequently formed with the addition of 1 mM D -dCTP or its L -analogs: L -dCTP, (–)3TC-TP, (–)3TC-PPNP, (–)FTC-TP and (–)FTC-PPNP. Notably, non-catalytic metal ions Ca(II), rather than catalytic metal ions Mg(II), have been used regularly to trap incoming nucleotides in pre-insertion ternary complexes with Dpo4 (28–31) and other DNA polymerases (32–35). (–)3TC-TP and (–)FTC-TP were synthesized and purified by Gilead Sciences with >95% purity (HPLC).…”
Section: Methodsmentioning
confidence: 99%
“…14 Two of the studies reported that the analog was not within hydrogen-bonding distance of adenine despite the opportunity to do so: Xia et al described an RNA duplex (measured at 1.61 Å resolution) containing the difluorotoluene base paired opposite adenine. 13a Although directly adjacent in a pairing configuration, the two “bases” were found not to approach one another within van der Waals distance, showing no evidence for attractive pairing interaction. Similarly, Irimia et al reported a co-crystal structure of the Dpo4 polymerase bound to DNA containing F opposite adenine (2.8 Å resolution).…”
Section: Introductionmentioning
confidence: 97%